DEVELOPING GEOMETRY LEARNING MATERIALS USING GUIDED INDUCTIVE INQUIRY MODEL FOR GRADE VIII STUDENTS OF JUNIOR HIGH SCHOOL - Vidiya Rachmawati; Himmawati Puji Lestari (Universitas Negeri Yogyakarta, 2016)
This study was aimed at developing and describing appropriate geometry learning materials in the forms of lesson plans and student worksheets using guided inductive inquiry model for grade VIII students of Junior High School. It is classified as Research and Development study based on 4D model which includes four stages that are define, design, development, and dissemination. The results of materials assessment show that the materials are considered appropriate and meet the minimum criteria of good lesson plans and student worksheets. From the 5 scale, the mean score of lesson plans is 4.62 and considered “very good”. Meanwhile, the mean score of student worksheets is 4.48 and considered “very good”. Both lesson plans and student worksheets were assessed by two experts and one mathematics teacher. The results of questionnaires from the students and the teacher towards the learning materials show that the learning materials is considered practical with score of 4.25 from the 5 scale, which mean “very good”. The results of learning observation questionnaires show that the learning materials is considered “very good”, in which the average percentage is 93.3%. On the other hand, the results of students’ achievement test show that the learning materials is considered effective as 87.5% of students’ score passed the minimum criteria of good mastery. Keywords: learning materials, guided inductive inquiry, geometry